ESTIMATING THE COST OF EQUITY IN THE BALTIC REGION - Mongrut, Samuel; Paškevičius, Arvydas; Dubinskas, Petras; Kovalevskaja, Renata; Fuenzalida, Darcy (Ekonomika, 2010)
During the last two decades the Baltic region has been subject to several episodes of investment volatility and political turmoil. Although financial liberalization processes undertaken in these countries could reduce the cost of equity, it seems that investors have been cautious in investing in the Baltic region. In this research, we estimate the cost of equity per industry sector in three Baltic countries (Estonia, Lithuania and Latvia) during the period 2005–2008 and conclude that the cost of equity seems to have increased during the period 2005–2007, indicating that the region was less financially integrated with the world capital market.